Trichostatin A Enhances Differentiation of Human Induced Pluripotent Stem Cells to Cardiogenic Cells for Cardiac Tissue Engineering. (24th July 2013) - Lim, Shiang Y.; Sivakumaran, Priyadharshini; Crombie, Duncan E.; Dusting, Gregory J.; Pébay, Alice; Dilley, Rodney J.
Abstract : This study identified a novel strategy to enhance cardiac differentiation of human induced pluripotent stem (iPS) cells by treating embryoid bodies with a histone deacetylase inhibitor, trichostatin A (TSA). It was found that cardiomyogenic differentiation of human iPS cells can be enhanced by TSA, and the cardiomyocytes so derived can be used to engineer vascularized, three‐dimensional contracting tissue. This tissue could be used for studying the pathophysiology of cardiac disease, for drug discovery test beds, and potentially for generation of cardiac grafts to surgically replace damaged myocardium. Abstract : Human induced pluripotent stem (iPS) cells are a promising source of autologous cardiomyocytes to repair and regenerate myocardium for treatment of heart disease. In this study, we have identified a novel strategy to enhance cardiac differentiation of human iPS cells by treating embryoid bodies (EBs) with a histone deacetylase inhibitor, trichostatin A (TSA), together with activin A and bone morphogenetic protein 4 (BMP4). Over a narrow window of concentrations, TSA (1 ng/ml) directed the differentiation of human iPS cells into a cardiomyocyte lineage. TSA also exerted an additive effect with activin A (100 ng/ml) and BMP4 (20 ng/ml). The resulting cardiomyocytes expressed several cardiac‐specific transcription factors and contractile proteins at both gene and protein levels. Functionally, the contractile EBs displayed calcium cycling and were responsive to the chronotropic agents isoprenaline (0.1 μM) and carbachol (1 μM). Implanting microdissected beating areas of iPS cells into tissue engineering chambers in immunocompromised rats produced engineered constructs that supported their survival, and they maintained spontaneous contraction. Human cardiomyocytes were identified as compact patches of muscle tissue incorporated within a host fibrocellular stroma and were vascularized by host neovessels. In conclusion, human iPS cell‐derived cardiomyocytes can be used to engineer functional cardiac muscle tissue for studying the pathophysiology of cardiac disease, for drug discovery test beds, and potentially for generation of cardiac grafts to surgically replace damaged myocardium.